Adolescents' Family Socioeconomic Status, Teacher–Student Interactions, and Career Ambivalence/Adaptability: A Three-Wave Longitudinal Study. (April 2023) - Zheng, Lifen; Meng, Haoran; Wang, Shaofan; Liang, Yue; Nie, Ruihong; Jiang, Lianjiang; Li, Beilei; Cao, Hongjian; Zhou, Nan
Using three-wave longitudinal data, this study tested the potential mediating roles of teacher–student relationship quality and teachers' career support efficacy in the association between Chinese adolescents' family socioeconomic status (SES) and career development ( N = 1410). Results showed that adolescents' family SES at Wave 1 was negatively associated with their career ambivalence at Wave 3 via positive associations with both teacher–student relationship quality and teachers' career support efficacy at Wave 2. Moreover, adolescents' family SES at Wave 1 was positively related to career adaptability at Wave 3 via its positive association with teachers' career support efficacy at Wave 2. This study highlighted the important role of teacher–student interaction in adolescents' career development.